Inhibition Capacity of the n-Hexane Fraction of Myrmecodia pendens as a Potential Anti-Cancer in Breast and Cervical Cancer: In Vitro Study - Bashari, Muhammad Hasan; Yuniarti, Eveline; Putri, Tenny; Qomarilla, Nurul; Kurnia, Dikdik; Satari, Mieke Hermiawati; Sahiratmadja, Edhyana Kusumastuti; Huda, Fathul (Indonesian Society for Cancer Chemoprevention, 2020)
Breast cancer (BC) and cervical cancer (CC) have a high prevalence and mortality rate worldwide. Despite the availability of advanced treatment, resistance to conventional chemotherapies has emerged. Myrmecodia pendens, one of the species of Sarang Semut (local name), possess a potential of antitumor effects by inducing cell death different cancer cell entities. This study aimed to assess anti-tumor activities of n-hexane fraction of M. pendens in inhibiting cell survival and cell migration in BC and CC cells. M. pendens was extracted in methanol then fractionated using n-hexane or ethyl acetate. BC cells including MCF-7 (luminal A), HCC-1954 (HER2+) cells and CC Hela cells were treated with M. pendens extracts to evaluate cytotoxic activity using 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay as well as anti-cell migration using scratch assay. We also analyzed inhibitory concentration 50 (IC50) of n-hexane fraction in BC and CC cells. We started with comparing cytotoxicity activities of methanol extract, ethyl acetate and n-hexane fractions of M. pendens. Data showed that the n-hexane fraction was the most potent inducing BC cell death. Therefore, we used the n-hexane fraction for further experiments. Interestingly, IC50 of this fraction in HCC-1954 and Hela cells were lower than in MCF-7 cells, 16; 13 and 60 ppm, respectively. Moreover, the low concentrations of n-hexane fraction inhibited HeLa cells migration, compared to control group (p<0.05). The n-hexane fraction of M. pendens shows promising anti-cancer agent, by inhibiting BC and CC cell survival as well as inhibiting CC cells migration.Keywords: breast cancer, cervical cancer, MTT assay, Sarang Semut, scratch assay